Recent progress on two-dimensional van der Waals thermoelectric materials with plasticity - Shengbo Yin; Cuihua Zhao; Bo-Ping Zhang; Wenbo Zhao; Chencheng Zhang; Linji Li (Journal of Materiomics)
Lots of research on thermoelectric materials (TEs) has focused on improving their thermoelectric (TE) properties to achieve efficient energy conversion. However, the mechanical properties of materials are also the object of concern in practical applications. Nowadays, the field of electronic devices is obviously developing in the direction of flexible electronics, so the research on TEs should also consider the plasticity. Since 2018, it has been discovered that inorganic semiconductor materials have the ability of plastic deformation, giving new possibilities for the development of TEs with plasticity. This paper focuses on the TEs with two-dimensional van der Waals (2D vdW) crystal structures, which have good plasticity but low TE properties. However, these materials have the potential to become excellent materials with TE properties and good plasticity through optimization strategies. In this paper, the latest research progress of 2D vdW TE materials and their applications in electronic devices are reviewed. The plasticity and TE properties of 2D vdW materials with M2X, MX and MX2 structure are summarized, and their plasticity mechanisms are discussed. We also introduce the application of high throughput screening in the discovery of novel 2D vdW plastic materials, and outline the future research work of 2D vdW TE materials.